Boundary layer effects on acoustic liners for turbofan engines: from experimental methods to optimization techniques - Spillere, André Mateus Netto (2022)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Mecânica, Florianópolis, 2022.